1999
DOI: 10.1136/gut.45.2.252
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of matrilysin (MMP-7) to the metastatic pathway of human colorectal cancers

Abstract: Background/Aim-Matrilysin is one of the matrix metalloproteinases that has a critical role in tumour invasion, and is often expressed in gastrointestinal cancers. The aim of this study was to examine the role of matrilysin in metastasis of human colorectal cancers. Patients (Subjects)/Methods-The relation between matrilysin expression and Dukes's type was investigated immunohistochemically in 83 surgically resected colorectal cancers, including five with liver metastasis. Moreover, the eVects of matrilysin on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
120
2
11

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(141 citation statements)
references
References 31 publications
8
120
2
11
Order By: Relevance
“…In the immunohistochemical detection of MMPs the focus has been on the analysis of MMP localisation. Correlations have been described between MMP-1 immunoreactivity and survival (Murray et al, 1996) and also between stage of disease and immunoreactivity for MMP-1 (Shiozawa et al, 2000), MMP-2 (Levy et al, 1991) and MMP-7 (Adachi et al, 1999). These studies measure MMP immunoreactivity without discrimination between latent proenzyme and activated enzyme.…”
mentioning
confidence: 99%
“…In the immunohistochemical detection of MMPs the focus has been on the analysis of MMP localisation. Correlations have been described between MMP-1 immunoreactivity and survival (Murray et al, 1996) and also between stage of disease and immunoreactivity for MMP-1 (Shiozawa et al, 2000), MMP-2 (Levy et al, 1991) and MMP-7 (Adachi et al, 1999). These studies measure MMP immunoreactivity without discrimination between latent proenzyme and activated enzyme.…”
mentioning
confidence: 99%
“…Matrilysin (MMP-7) is a member of the MMP gene family, and has proteolytic activity against a wide spectrum of substrates such as collagens, proteoglycans, elastin, laminin, fibronectin and casein (Woessner and Taplin, 1988;Miyazaki et al, 1990;Wilson and Matrisian, 1996). It is produced by malignant tumour cells such as oesophageal, gastric, colorectal, head and neck, lung, prostate and hepatocellular carcinomas (Yamamoto et al, 1997;Adachi et al, 1998;Yamashita et al, 1998;Adachi et al, 1999;Babletz et al, 1999;Yamamoto et al, 1999). Immunohistochemical studies have shown that the expression of matrilysin correlates significantly with nodal or distant metastasis in gastric and colorectal carcinomas (Adachi et al, 1998Yamashita et al, 1998).…”
mentioning
confidence: 99%
“…15,29 MMP-7 is constitutively expressed in exocrine and mucosal epithelial cells in the skin, pancreas, liver, breast, intestine, and lung. In cancers of the colon, [30][31][32][33] esophagus, 34 stomach, [34][35][36] pancreas, 37 breast 38 and prostate, 39 increased MMP-7 expression is associated with tumor invasion, cancer progression, and poor prognosis. Two mechanisms may be responsible for the enhancement of cancer invasion and metastasis by MMP-7: direct effects of MMP-7 proteinase activity and indirect effects of MMP-7, such as activation of MMP-2 and MMP-9.…”
Section: Discussionmentioning
confidence: 99%